The inflation target and the structure of labour markets: Implications for common monetary policy - Juha Kilponen (Bank of Finland, 1999)
Both the optimal inflation target and the optimal degree of output stabilization are found to be conditional on the prevailing wage bargaining structure.If monopolistic wage setters act as strategic leaders of the monetary policy game, an explicit inflation targeting regime removes inflation bias from monetary policy, but does not remove the trade-off related to average level of output and output stabilization.In contrast to usual results on inflation targeting, appointing a central banker who is more conservative than the government leads to welfare gains for society.If centralization within the national labor markets increases in the common monetary policy area, the monetary policy game with regard to the European Central Bank might be conducted under the strategic leadership of trade union confederations.This leads to a Pareto loss.
URN:NBN:fi:bof-20140807377
Keywords: 330; monetary policy; labor markets; European Monetary Union; inflation targeting